Otimização da eletro-oxidação controlada de metano sobre a superfície de eletrodos de ouro visando a formação de moléculas de valor agregado - Andrade, Renato Nunes de (2023)
OPTIMIZATION OF THE CONTROLLED ELECTROOXIDATION OF METHANE ON THE SURFACE OF GOLD ELECTRODIES FOR THE FORMATION OF VALUE-ADDED MOULECULES: This work aims to contribute to the understanding of the partial electrooxidation of methane to methanol. The challenge of this proposal is the unfavorable reaction kinetics of this hydrocarbon in oxidizing due to its tetrahedral and non-polar molecular geometry. These factors make it difficult to break the carbon-hydrogen bond to form methyl radicals followed by the addition of oxygen, and another aspect is the molecule's low solubility in water. The most common process for obtaining methanol is by reforming methane, which requires high temperatures (700 to 1100 ºC). However, electrocatalyst systems are a promising alternative, given their ability to do this under milder conditions (25 ºC and 1 atm). In this thesis, an H-shaped electrochemical cell system was used to collect data by varying the pH, type of electrolyte, concentration and cell potential in order to create a data set that could predict, using linear and polynomial regression algorithms and support vector machines, which condition would be the most favorable for methanol production on the gold electrodes surface. In this sense, 0.1 M lithium carbonate at a potential of 0.2 V vs. Ag|AgCl and 0.1 M potassium hydroxide at a potential of 1.0 V vs. Ag|AgCl were the most promising production systems. Furthermore, the literature has always credited potential and pH as determining factors in the selectivity of electrochemical reactions, but this study shows that the radius of the cation in the selected material plays a much more important role in the electrooxidation of methane to methanol. Finally, this is a technology that can be developed in synergy with the already prestigious green hydrogen (GH2), which uses renewable or clean energy, through photoelectrocatalysis of solar energy. However, the advantage of methanol is that it is easy to store as it is a liquid, rather than an explosive gas like H2(g).